Answer:
The solution of the given quadratic equation is 1 and (-10).
Step-by-step explanation:
[tex]2x^2+18x=20[/tex]
[tex]x^2+9x=\frac{20}{2}[/tex]
[tex]x^2+9x-10=0[/tex]
[tex]ax^2+bx+c=0[/tex]
Solving equation by quadratic formula:
Here , a = 1,b = 9, c = (-10)
[tex]D=b^2-4ac=(9)^2-4(1)(-10)=121[/tex]
[tex]x=\frac{-b+{\sqrt{D}}}{2a}=\frac{(-9)+\sqrt{121}}{2(1)}=1[/tex]
[tex]x=\frac{-b-{\sqrt{D}}}{2a}=\frac{(-9)-\sqrt{121}}{2(1)}=(-10)[/tex]
The solution of the given quadratic equation is 1 and (-10).